Physical Characters of Trees And Their Effects on Micro-Climate (Case Study at Urban Forest and Green Open Space at Semarang City) - Endes N Dahlan (Forum Geografi, 2014)
Air temperature in cities are increasing which can cause reduce the human comfort and productivity. Urban forest can make the environment comfortable. The objectiveof the researc hwere: (1). To Determine the effects of urban forest on air temperature and relative humidity, (2). To analyze the effects of physical characters of trees ont he micro-climate amelioration and(3). To Determine species of trees which are very effective for micro-climate amelioration.The results of the research revealed that the average of daily air temperature in the urban forest was 30.2 C with arelative humidityof 74.0%, while the daily air temperature around the urban forest was 31.8 Karakter Fisik Pohon ... (Dahlan E) o C with relative humidityof 71.1%. Tree composisitin of all study sites consist of192trees, 29 speciesand 13families. The TinjomoyoForest Tourism has the highest density of trees(406trees/ha), while the lowest in the Parks Minister Supeno (316trees/ha). Value of Key Performance Indicator (KPI) of trees based on calculation of tall of trees, diameter of canopies, total leaves area and canopy forms noticed that very effective trees for micro-climate amelioration were: Angsana(Pterocarpus indicus), beringin(Ficus benjamina), flamboyan(Delonix regia) , ketapang(Terminalia catappa), mahoni (Swietenia mahogany), andtrembesi (Albizia saman).